Tourist Visitation Impact: Unveiling the Role of Domestic and Foreign Visitors in Shaping Hotel Tax Revenue in Bandung - Irawan, Arry; Suwondo, Sulistia; Kusumastuti, Endah Dwi (Indonesian Journal of Economics and Management, 2023)
The city of Bandung, nicknamed Paris van Java, is a tourism destination in West Java. This city has advantages in terms of physical and cultural, making it an alternative to be visited by domestic and foreign tourists. For the Bandung city government, the visit of domestic and foreign tourists has the potential to increase local revenue sources, especially from local taxes. Local taxes that may arise from the number of tourist visits are hotel taxes. This study seeks to further explore the role of domestic tourist visits in increasing hotel tax revenues in the city of Bandung. This study uses descriptive and causal methods and uses a quantitative approach. The data used is secondary data with a time series from 2003 to 2019. Data analysis with multiple linear regressions and SPSS version 18 application assistance. The results show that partially domestic tourist visits have a significant effect on hotel tax receipts and foreign tourist visits do not have a significant effect. significant to hotel tax revenue in the city of Bandung. Meanwhile, domestic and foreign tourist visits have a significant effect on hotel tax revenues in the city of Bandung.